Molecular dynamics research of size dependence of the melting temperature of silicon nanoparticles - I.V. Talyzin; M.V. Samsonov; S.A. Vasilyev; M.Yu. Pushkar; V.V. Dronnikov; V.M. Samsonov (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2018)
Size dependence of the melting temperature of Si nanoparticles has been investigated combining molecular dynamics and thermodynamic simulations. The results of the atomistic simulation obtained using the Stillinger-Weber potential agree with the results of other authors and with the thermodynamic simulation results based on Thomson’s formula. These results predict that the melting temperature Tm of Si nanoparticles diminishes with increasing their reciprocal radius R-1 following to the linear law. The available experimental data predict much lower values of Tm, including underestimated values of the limiting value Tm(∞) found by means of the linear extrapolation of experimental dots to R-1 → 0 (i.e. to the particle radius R → ∞), and the underestimation of Tm(∞) ranges from 200 to 300 K in comparison with the melting point 1688 K of the bulk crystalline Si. Taking into account the obtained results and their comparison with available results of other authors, a conclusion is made that molecular dynamics results, obtained by using the Stillinger-Weber potential, should be more adequate than the available experimental data on the melting temperature of Si nanoparticles.